YAP1-MAML2 Fusion as a Diagnostic Biomarker for Metaplastic Thymoma - Zhao, Jikai; Zhao, Ruiying; Xiang, Chan; Shao, Jinchen; Guo, Lianying; Han, Yuchen (Frontiers in Oncology, 2021)
Background: Metaplastic thymoma is a very rare tumor with only a few case reports documented in literature. Hence, its molecular features have not been well explored. Materials and methods: Seventeen specimens of metaplastic thymoma were sequenced and retrospectively analyzed by fluorescence in situ hybridization (FISH) and immunohistochemistry retrospectively in the study. In addition, seven cases of micronodular thymoma with lymphoid stroma and nine cases of type A thymoma were also investigated. Results: Among these metaplastic thymomas, fifteen cases showed classical histological features, and two cases displayed characteristic micronodular-like growth patterns. DNA and RNA based next-generation sequencing identified and confirmed highly recurrent Yes Associated Protein 1 (YAP1) - Mastermind Like Transcriptional Coactivator 2 (MAML2) translocation (13/17, 76.5%) in metaplastic thymoma but not in micronodular thymoma with lymphoid stroma (0/7, 0%) and type A thymoma (0/9, 0%). In addition, six nonsense mutations were also detected in the metaplastic thymoma. FISH in microdissection specimens indicated that both epithelioid and spindle cell components harbored YAP1-MAML2 gene rearrangements. Conclusions: Our study explored the genetic alterations in epithelioid and spindle cell components in metaplastic thymomas. Furthermore, YAP1-MAML2 gene rearrangements emerged as a potential diagnostic biomarker helpful for distinguishing metaplastic thymoma from type A and micronodular thymoma with lymphoid stroma.